The emergence of acid ceramidase as a therapeutic target for acute myeloid leukemia. (3rd June 2017) - Tan, Su-Fern; Pearson, Jennifer M.; Feith, David J.; Loughran, Thomas P.
ABSTRACT: Introduction : Acute myeloid leukemia (AML) is the most common adult leukemia. Only a fraction of AML patients will survive with existing chemotherapy regimens. Hence, there is an urgent and unmet need to identify novel targets and develop better therapeutics in AML. In the past decade, the field of sphingolipid metabolism has emerged into the forefront of cancer biology due to its importance in cancer cell proliferation and survival. In particular, acid ceramidase (AC) has emerged as a promising therapeutic target due to its role in neutralizing the pro-death effects of ceramide. Areas covered : This review highlights key information about AML biology as well as current knowledge on dysregulated sphingolipid metabolism in cancer and AML. We describe AC function and dysregulation in cancer, followed by a review of studies that report elevated AC in AML and compounds known to inhibit the enzyme. Expert opinion : AML has a great need for new drug targets and better therapeutic agents. The finding of elevated AC in AML supports the concept that this enzyme represents a novel and realistic therapeutic target for this common leukemia. More effort is needed towards developing better AC inhibitors for clinical use and combination treatment with existing AML therapies.